Generation and evaluation of a chimeric antibody against coxsackievirus and adenovirus receptor for cancer therapy. Issue 11 (28th September 2019) - Sakamoto, Shuichi; Inoue, Hiroyuki; Kaneko, Mika K.; Ogasawara, Satoshi; Kajikawa, Masunori; Urano, Sakiko; Ohba, Shun‐ichi; Kato, Yukinari; Kawada, Manabu
Abstract: Coxsackievirus and adenovirus receptor (CAR) is a single‐pass transmembrane protein that is associated with adenoviral infection. CAR is involved in the formation of epithelial tight junctions and promotes tumor growth in some cancers. Previously, we developed mouse monoclonal antibodies against human CAR and found that one, mu6G10A, significantly inhibited tumor growth in xenografts of human cancer cells. Herein, we generated and characterized a mouse‐human chimeric anti‐CAR antibody (ch6G10A) from mu6G10A. ch6G10A had binding activity, inducing antibody‐dependent cellular cytotoxicity and complement‐dependent cytotoxicity, and in vivo anti‐tumor activity against CAR‐expressing prostate cancer DU‐145 cells. In addition, cancer tissue array analysis confirmed that CAR is highly expressed in neuroendocrine lung cancers including small cell lung cancer, and treatment with ch6G10A effectively inhibited in vivo subcutaneous tumor growth of NCI‐H69 small cell lung cancer cells in nude mice. Moreover, treatment with mu6G10A effectively inhibited both in vivo orthotopic tumor growth and distant metastatic formation in mouse xenograft models of a highly metastatic subline of human small cell lung cancer DMS273 cells. These results suggest that targeting therapy to CAR with a therapeutic antibody might be effective against several cancer types including small cell lung cancer. Abstract : We describe the generation of a mouse‐human chimeric anti‐CAR antibody and evaluation of anti‐tumor activities of these antibodies. Our results suggest that targeting therapy to CAR with therapeutic antibodies might be effective against several cancers including small cell lung cancer.